THE IMAGE OF NICARAGUA AND NICARAGUANS IN THE FIRST TEXT USED IN THE TEACHING OF NATIONAL HISTORY (Andamios, Revista de Investigación Social, 2009)
After presenting some considerations on the importance of schools and in particular history textbooks in the formation of a national conscience and the creation and consolidation of a sense of nationality, in this article we analyze the first book used in Nicaragua as a textbook for teaching Nicaraguan history and geography, at the end of the 19th Century. We consider this book, Notas geográficas y económicas sobre la república de Nicaragua (Geographical and economical notes on the Nicaragua republic), written by a French engineer, Paul Lévy, to be one of the first textual images of that Central American country, reflecting the vision and concept that Nicaraguan elites of that time had of their own country.
Keywords: Teaching national history; concept and image of the nation; Nicaragua national history textbooks of the 19th century